2020
DOI: 10.1021/acsearthspacechem.0c00113
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of the Permian Oil Shale in the Northern Bogda Mountain, Junggar Basin, Northwest China: Implications for Weathering, Provenance, and Tectonic Setting

Abstract: The northern Bogda Mountain is located in the southern margin of the Junggar Basin in northwest China. Based on inorganic geochemistry of oil shale samples of the Middle Permian Lucaogou Formation, the depositional environment, weathering degree, the provenance, and tectonic background of the northern Bogda Mountain were determined. The oil shale in the study area was formed in the deep lake environment. The major and trace element ratios suggest that the oil shale was deposited under semi-humid to humid/warm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
(113 reference statements)
1
6
0
Order By: Relevance
“…42−44 When the climatic conditions change from warm to dry, the evaporation of water gradually increases, and the elements precipitate in the form of salts, resulting in a relative high content of these elements in the sedimentary rocks. 45,46 The marked depletion in these elements relative to UCC also indicates a semihumid to humid/warm climate in the source area of high quality oil shale layers (Figure 5a). 5.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42−44 When the climatic conditions change from warm to dry, the evaporation of water gradually increases, and the elements precipitate in the form of salts, resulting in a relative high content of these elements in the sedimentary rocks. 45,46 The marked depletion in these elements relative to UCC also indicates a semihumid to humid/warm climate in the source area of high quality oil shale layers (Figure 5a). 5.5.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the high quality oil shales mainly occurred in a semihumid to humid/warm climate, whereas low quality oil shales were deposited under a semihumid to semiarid paleoclimate (Figure f). When the climate is warm and humid, the dissolved amounts of Sr, V, Ni, and Ba are relatively large. When the climatic conditions change from warm to dry, the evaporation of water gradually increases, and the elements precipitate in the form of salts, resulting in a relative high content of these elements in the sedimentary rocks. , The marked depletion in these elements relative to UCC also indicates a semihumid to humid/warm climate in the source area of high quality oil shale layers (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic geochemical indicators such as P, Cu, Cd and Ni are positively correlated with TOC and have been applied to indicate the relative bioproductivity evolution of ancient lakes (Tyrrell, 1999;Li et al, 2020). The P/Ti and Cd/Al ratios have been widely adopted as indices of water bioproductivity, with high ratios indicating high lake bioproductivity (Zeng et al, 2015;Fathy et al, 2018).…”
Section: Primary Bioproductivitymentioning
confidence: 99%
“…In recent years, research on the oil shale in the northern Bogeda Mountains has been documented; this work has determined that the oil shale in the Lucaogou Formation was mainly deposited in an offshore lacustrine environment and that the oil shale development was well to excellently correlated with the continuous subsidence and lake expansion in the northern Bogeda Mountains of Junggar Basin. , …”
Section: Introductionmentioning
confidence: 99%
“…12,13 In recent years, research on the oil shale in the northern Bogeda Mountains has been documented; this work has determined that the oil shale in the Lucaogou Formation was mainly deposited in an offshore lacustrine environment and that the oil shale development was well to excellently correlated with the continuous subsidence and lake expansion in the northern Bogeda Mountains of Junggar Basin. 14,15 The studies described above were mainly focused on the macroscopic geological settings of oil shale formations. During the depositional period of the Lucaogou Formation, the foreland of the Junggar Basin was in its largest subsidence stage and was experiencing underfilling conditions.…”
Section: Introductionmentioning
confidence: 99%